Assessment of organochlorine pesticide residues in fish samples from the Okavango Delta, Botswana - Mpofu, Christopher (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
This thesis presents an evaluation of the dispersive solid-phase extraction (d-SPE) method referred to as the quick, easy, cheap, effective, rugged and safe (QuEChERS) method for the determination of four organochlorine pesticide residues in fish samples. The pesticides investigated in this study were o, p"²-DDT, p, p"²-DDE, aldrin and dieldrin. The combined use of Gas Chromatography with an Electron Capture Detector (GC-ECD) and sensitive Time of Flight (TOF) mass detector facilitated the identification of the target analytes. In the absence of certified reference material, the overall analytical procedure was validated by systematic recovery experiments on spiked samples at three levels of 2, 5 and 10 ng/g. The targeted compounds were successfully extracted and their recovery ranged from 76 to 96% with relative standard deviations of less than 13%. The optimum QuEChERS conditions were 2g of fish powder, 10 ml acetonitrile and 1 min shaking time. The optimal conditions were applied to assess the levels of chlorinated pesticides in blunt-tooth catfish (Clarias ngamensis), tigerfish (Hydrocynus vittatus), Oreochromis andersonii and red-breasted tilapia (Tilapia rendalli) from the Okavango Delta, Botswana. Dieldrin, p, p"²-DDE and aldrin were detected in all the analysed samples with a concentration range of 0.04 "“ 0.29, 0.07 "“ 0.33, 0.04 "“ 0.28 and 0.03 "“ 0.24 ng/g per dry weight in O. andersonii, C. ngamensis, T. rendalli and H. vittatus respectively. These concentrations were below the US-EPA 0.1 Î¼g/g allowable limit in edible fish and the Australian Maximum Residue Limit (MRL) of 50 - 1000 ng/g in fresh fish. DDT was not detected in all the fish species investigated. The mean lipid content recorded in the fish samples were 1.24, 2.16, 2.18 and 4.21% for H. vittatus, T. rendalli, O. andersonni and C. ngamensis respectively. No systematic trend was observed between fish age and pesticide levels in fish. Acetylcholinesterase (AChE) activity assays were performed to assess the effects of organochlorine pesticides in Clarias ngamensis. The enzyme activity recorded in Clarias ngamensis from the Okavango Delta and the reference site was 12.31 Î¼mol of acetylcholine iodide hydrolysed/min/g brain tissue. The enzyme activity remained the same indicating no enzyme inhibition. The conclusions drawn from this study are that the QuEChERS method is applicable for the determination of organochlorine pesticide residues in fish matrices. The fish from the Okavango Delta are safe for human consumption.
Keywords: Pesticides; Organochlorine compounds; Freshwater fishes -- Effect of pesticides on -- Botswana -- Okavango River Delta; Water -- Pesticide content -- Botswana -- Okavango River Delta; Catfishes -- Botswana -- Okavango River Delta; Tigerfish -- Botswana -- Okavango River Delta; Redbreast tilapia -- Botswana -- Okavango River Delta